Socialist Globalization in Mozambique: A Cosmopolitan Perspective on Technical-Labor Internationalism in the Late Cold War Era - Mora Silva, Julimar (International review of social history, 2025)
This article examines socialist globalization from the perspective of technical-labor internationalism in Mozambique, focusing on the final stage of the Cold War. First, it analyzes the four main pathways through which international technicians arrived in Mozambique: Latin American exile, socialist intergovernmental cooperation, European postcolonial humanitarianism, and African regionalism. It offers a cosmopolitan perspective on the relations that socialist Mozambique forged with the world. It then provides an inventory of the models of integration of these international technicians into the Mozambican state apparatus, presenting a framework emphasizing organizational rather than ideological aspects. It concludes that, while these paths were singular, they were not mutually exclusive. More importantly, they were instrumental in shaping the political affinities and frictions between international technicians in that cosmopolitan universe.